Metabolic and chemical studies on α,N-diarylnitrones - (:unkn) unknown (My University, 1994)
The metabolism of a number of α,N-diarylnitrones has been studied in vitro using male hamster microsomes. All substrates produced benzaldehyde and an uncharacterised substance as metabolites. If the metabolic reaction was carried out in the light, or if the metabolic extracts were exposed to light, the chemical formation of two new compounds was observed. One compound had chromatographic and spectroscopic properties identical to the corresponding amide; the other compound had properties which suggested it was an oxaziridine. The results are discussed in relation to the formation of amides as metabolites of N-benzyl anilines. It is concluded that nitrones are not on the above metabolic pathway, but that they may form amides by chemical rearrangement. © Freund Publishing House Ltd., 1994
Keywords: diarylnitrones; hamster; in vitro metabolism; metabonates; microsomes; N-benzoylanilines; oxaziridines